1996
DOI: 10.1063/1.363572
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz ballistic current oscillations for carriers with negative effective mass

Abstract: It is shown that the stationary distribution of ballistic current carriers moving across a thin doped base is unstable if there exists a negative effective mass (NEM) part in the carrier dispersion law. Under such a condition, a regime with a quasistationary current oscillations is established for a wide range of voltages across ballistic diode. The oscillation frequency and amplitude depend on the base length, doping concentration, and applied voltage. The current oscillations take place in a short-circuit re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 7 publications
0
26
0
Order By: Relevance
“…[3][4][5][6] Most recently, two designs of the ballistic terahertz ͑THz͒ generators based on the nonparabolic NEM hole dispersion have been suggested. 7 Theoretically, using a model hole dispersion relation with a NEM region, Vagidov et al [8][9][10][11] carried out a series of calculations of hole ballistic transport in thin p ϩ pp ϩ doped diodes by using the Poisson equation and the collisionless Boltzmann equation. It is indicated, under certain biases, sta-tionary concentration distributions of the ballistic holes in p ϩ pp ϩ structures hold a self-organized region where holes with NEM predominate.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] Most recently, two designs of the ballistic terahertz ͑THz͒ generators based on the nonparabolic NEM hole dispersion have been suggested. 7 Theoretically, using a model hole dispersion relation with a NEM region, Vagidov et al [8][9][10][11] carried out a series of calculations of hole ballistic transport in thin p ϩ pp ϩ doped diodes by using the Poisson equation and the collisionless Boltzmann equation. It is indicated, under certain biases, sta-tionary concentration distributions of the ballistic holes in p ϩ pp ϩ structures hold a self-organized region where holes with NEM predominate.…”
Section: Introductionmentioning
confidence: 99%
“…To solve (1) with the boundary conditions (5), we adapted the numerical procedure called the splitting scheme [8], [9] (we used the cubic spline method for interpolations required in the method). The method allows to solve the Vlasov equation with the numerical accuracy of the order of Δt 2 , where Δt is the time step for the numerical simulation.…”
Section: Model and Methods Of Simulationmentioning
confidence: 99%
“…In addition, the carried out calculations showed that the Kramers degeneracy [6] of holes at k 2D || [110] is lifted for k 2D = 0 and there are two different branches of dispersion (4,5,6) lines correspond to holes with opposite spins relations corresponding to two different spin states as it is seen in Fig. 2 [7].…”
Section: Energy Dispersion Relations In Si Quantum Wellsmentioning
confidence: 99%
“…(1), may have self-organized oscillatory regimes only at certain ratio of two effective masses, m and M, -light and heavy effective masses, respectively. This ratio must satisfy the following inequality [5]:…”
Section: Introductionmentioning
confidence: 99%